Managing and Funding University Library in Nigeria - Olawale , Shittu, Taofeek; Sarah , Gbenu; Michael , Sessi, Abiodun (International Journal of Educational Management, 2025)
This paper examined the managing and funding university library in Nigeria Library is the heart of university system and repository centre for all academic institution. The objective of University library is to facilitate teaching and learning, and promote scholarship for end users in line with mission and vision of the University. Some public university libraries in Nigeria are bedeviled with critical challenges which culminated to poor management, insufficient fund, lack of trained personnel, destructive character of library users, high foreign exchange rate, dilapidated infrastructure, dwindling collection of library materials and poor automation of library system in meeting up with demand of 21st century. These problems include inability to provide internet facilities, obsolete computers hardware, epileptic supply of electricity, dilapidated library buildings and inadequate staff strength. The study concluded that University libraries in Nigeria are in need of sufficient fund to provide internet and automation facilities, modern building and stable supply of electricity. I is therefore recommended among others that University Librarian should boost Internally Generated Revenue and plan annual budget through financial support from government grants, private donors and philanthropist, endowments and consultancy fees for smooth running of library system.